Preparation of rigid cross-linked PVC foam with excellent thermal insulation through adding high-reflectivity IR opacifier. (8th February 2021) - You, Jiangan; Xing, Haiping; Xue, Jian; Jiang, Zhiwei; Tang, Tao
Abstract: For polymer foams with low-density, the thermal radiation propagating through the foam still contributes significant to the total thermal transfer. It is very promising to enhance the absorption or reflection of IR radiation by the foam matrix. However, it is still a question which of the reflected infrared or absorbed infrared is more effective in reducing radiative thermal conductivity. In this work, we studied theoretically and experimentally the effectiveness to reduce the radiative thermal conductivity of polymer foams by reflection mode and absorption mode. The relationship between the optical parameters of foam and the heat radiation transmission in the foams was quantitatively investigated. It was found that, taking into account the re-emission, the radiative thermal conductivity was further reduced merely by increasing the absorption coefficient, but in theory it could continue to drop to zero by increasing the reflection fraction. Both the flake aluminum powder (FAP) that mainly reflects infrared and the flake graphite powder (FGP) that mainly absorbs infrared were added to the rigid cross-linked PVC (c-PVC) foam. The results demonstrated that the reduction of radiative thermal conductivity of the c-PVC foam with FAP was more significant than of the c-PVC foam with FGP. The experimental results were in good agreement with the theoretical prediction. Graphical abstract: Image 1